Nutritional policies and anaemia among under-five children in selected south Asian countries: 1950-2016 - Hanumant Waghmare; Nasim Ahamed Mondal; Babul Hossain (BMC, 2022)
Abstract Background Despite policies and social development, childhood malnutrition remains a significant public health and social challenge in many south Asian countries. Also, there is a lack of study for a comparative understanding between the nutrition policies and nutritional status of under-5 children in south Asian countries. In this context, the present study aims to understand the comparative evolution of nutritional policies and programs in south Asian countries between 1950 to 2016 and assess current nutritional status of children under the age of 5 in Bangladesh, India, Nepal, and Pakistan. Methods This study obtained yearly anaemia data from the Global Health Observatory Data Repository (World Health Statistics) from 1990 to 2016 for comparative analysis. The most recent Demographic Health Survey (DHS) rounds have been taken for four south Asian nations. Bivariate analysis and classical figures have been utilised to demonstrate the findings. Results In Bangladesh, Nepal, India, and Pakistan, the prevalence of anaemia decreased by 33%, 31%, 20%, and 12% from 1990 to 2016, respectively. While analysis of the policy and programs, the problem of under-nutrition in all selected countries stems from the lack of serious implementation of National Nutrition Policies. Conclusion This study suggests that the national nutrition programs require inter-sectoral coordination between central ministries within countries to reduce the anaemia level. In light of Sustainable Development Goals (SDG), a multi-faceted policy should be implemented to prevent and control malnutrition problems in these countries.